1998
DOI: 10.1515/humr.1998.11.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of jocular instructional methods on attitudes, anxiety, and achievement in statistics courses

Abstract: This investigation examines the effects of using humor äs a systematic teaching strategy to improve attitudes, reduce anxiety, and increase achievement in introductory undergraduate and graduate statistics courses. A singlesample pretest-posttest design was employed to measure changes in attitudes and anxiety and their relationships to achievement levels. Three incidental samples of 142 students were selected to fest the humorous instructional Intervention. Statistically significant t-ratios in thepredicted di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 37 publications
0
45
0
1
Order By: Relevance
“…Berk and Nanda (1998) report statistically significant effects (and practically significant effect sizes) in the predicted directions for attitudes toward content and anxiety for statistics courses and moderate correlations with overall achievement as well.…”
Section: Types Of Funmentioning
confidence: 79%
“…Berk and Nanda (1998) report statistically significant effects (and practically significant effect sizes) in the predicted directions for attitudes toward content and anxiety for statistics courses and moderate correlations with overall achievement as well.…”
Section: Types Of Funmentioning
confidence: 79%
“…The articles by Lomax and Moosavi (2002) and Friedman et al (2002), along with others (e.g., Berk and Nanda, 1998;Forte, 1995;Lesser and Pearl, 2008;Schacht and Stewart, 1992), are extremely useful resources for teachers who wish to introduce humor into the statistics classroom. Humor can be used from the start of the course and used regularly during classes and on assessment items, although it is important that it is not overused.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging body of research suggests that certain types of fun items can be effective in improving statistics student attitudes and reducing student anxiety while increasing student interest, recall of material, and conceptual understanding (Berk 2009b;Berk & Nanda 1998Field 2010;Friedman, et al 2002;Garner 2006;Lomax & Moosavi 2002;Neumann, et al 2009). Other motivations from the literature reviewed by Lesser and Pearl (2008) include: building classroom community, reducing anxiety, humanizing the subject/instructor/course, fostering openness in the classroom, increasing students' attention and participation for the entire class period, providing a means of illustrating difficult concepts, and giving students a highly memorable way to recall specific content that will last well beyond the final exam (Friedman, et al 2002;Schacht & Stewart 1990).…”
Section: Motivationsmentioning
confidence: 99%
“…Lesser and Pearl (2008) provide a comprehensive overview of using fun in the statistics classroom, and the paper includes a table listing 20 modalities (with references or points of departure for each), implementation tips and some emerging evidence on potential effectiveness of some modalities. The accumulation of evidence is most established for the modality of humor and experimental studies of the pedagogical impacts of humor have shown significant positive outcomes in student ratings of the lesson, student ratings of the instructor, student anxiety, student attitudes towards statistics, and student recall and retention of information (Berk & Nanda 1998Garner 2006;Neumann, Hood & Neumann 2009). It is noted that the research on humor in the context of statistics is relatively recent in the overall four decades' worth of research on humor in educational settings (e.g., Banas, Dunbar, Rodriguez & Liu 2011).…”
Section: Introductionmentioning
confidence: 99%